Progress in defining the mechanism of action of antidepressants - Schwaninger, Markus; Weisbrod, Matthias; Knepel, Willhart (CNS drugs, 1997)
The mechanism of action of antidepressants is still unknown. The delayed onset of their therapeutic effect suggests that they act through an adaptive process. Recent research has demonstrated that neural plasticity and learning, which may underlie the induction of depression by repetitive psychosocial stress. involve gene transcription through the cyclic adenosine monophosphate (CAMP)— and calcium-responsive element (CRE) and its cognate transcription factor CREB. By downregulating β-adrenergic receptors linked to CAMP-formation and serotonin 5-HT2 receptors linked to intracellular calcium mobilisation and blocking voltage-dependent calcium channels, antidepressants can inhibit gene transcription through the CRE. Thus, modification of CRE-directed transcription may contribute to the therapeutic efficacy of antidepressants.
Elektronische Reproduktion der Druck-Ausgabe 18. November 2012
Gesehen am 23.12.2021